Analisis Sharia Compliance pada Produk Pembiayaan di PT. BPRS Amanah Ummah Leuwiliang Bogor - Ulfi Nurhalimah; Lili Puspitasari (Jurnal Maps (Manajemen Perbankan Syariah), 2023)
BPRS has a role in stabilizing the financial sector which can save the national economy. BPRS are required to be able to perform their functions properly, with this the Islamic macroeconomic system can be implemented properly. Sharia principles are very important in Islamic banking, because this is a factor for prospective customers in choosing financial products at Islamic banks themselves. Sharia compliance is the main key or basic principle for Islamic banks in carrying out their practices in Islamic banks. This study aims to analyze sharia compliance on financing products at PT. BPRS Amanah Ummah. The method used is descriptive qualitative research method based on the type of case study. Researchers use data collection techniques by observation, which will go directly to the field, then conduct interviews with sources in a structured manner and carry out technical documentation by testing the validity of the data using triangulation. The results of the study show that in business activities on financing products at PT. BPRS Amanah Ummah has fully complied with the principles of sharia compliance.